On the intersectionality of religious and racial discrimination: a case study on the applicability of ICERD with respect to China´s Uyghur muslim minority - Holder, Ross (Religion and human rights, 2019)
AbstractAs an officially recognised minority nationality in China, the Uyghurs' unique religious identity is ostensibly protected under Chinese national law. In reality, such protections are limited in practice, with frequent claims by Uyghur activists, human rights NGOs and scholars that government policies result in the religious discrimination of the Uyghur population in Xinjiang. In light of the inefficacy of state legislation in protecting the Uyghurs' religious freedoms, this article considers the protections offered within the Human Rights Treaty System of the United Nations (UN), of which China is both a charter member and an increasingly active participant. However, any attempt to consider Freedom of Religion or Belief protections within the UN's core treaties remains frustrated as China has yet to ratify the International Covenant on Civil and Political Rights, which is the sole UN human rights instrument to contain provisions dedicated to religious and minority rights. To overcome this issue, this article argues that acts of religious discrimination against the Uyghur minority may also fall into contention with the protections contained within the International Convention on the Elimination of All Forms of Racial Discrimination, a treaty that has been ratified by China and is therefore legally obligated to comply with.